Why EU Law Claims Supremacy. (24th April 2018) - Lindeboom, Justin
Abstract: This article explores the conception of law that underlies the case law of the Court of Justice of the European Union (CJEU), building on Opinion 2/13 on EU accession to the European Convention on Human Rights (ECHR) as a topical example. Joxerramon Bengoetxea's metaphor of the CJEU being a 'Dworkinian court' fails to explain fundamental aspects of the Court's case law which are incompatible with Dworkin's theory of law. Instead, the CJEU is committed to an EU legal system which conforms to Joseph Raz's theory of the necessary conditions for legal systems: comprehensiveness, openness and a claim of supremacy. Within this paradigm, the supremacy claim of EU law is in need of demystification because it is inherent to any legal system. Paradoxically, while Opinion 2/13 suggests that the EU should be given special treatment in its accession to the ECHR, the Court's underlying conception of the EU legal system is essentially mimetic of the typical characteristics of national legal systems. This mimetic nature of the EU legal system entails a dissociation between the political and the legal nature of the EU: while the EU is certainly not a state, its legal system is no different from national legal systems.